41.4k views
5 votes
I don't understand this​

I don't understand this​-example-1
User Ian Ross
by
5.4k points

1 Answer

4 votes

Answer:

(i) A"(-7, 6)

(ii) A"(3, 4)

Explanation:

(i) The notation is a bit different. We assume it to mean that the transformation X is a translation 4 left and 2 up. That is, (-4, 2) gets added to the (x, y) coordinates:

(x, y) ⇒ (x -4, y +2)

For the coordinates A(1, 2), a transformation by X gives ...

A'(1 -4, 2+2) = A'(-3, 4)

We believe the notation X² is supposed to signify a second transformation by X. Then a second transformation by X of A' gives ...

A"(-3 -4, 4 +2) = A"(-7, 6) . . . A transformed by X²

__

(ii) Reflection in the line x=0 negates the x-coordinate, so the transformation Y is ...

(x, y) ⇒ (-x, y)

Applying this transformation to the result of translating A by transformation X, we get ...

A" = (-(-3), 4) = A"(3, 4) . . . A transformed by XY

User Kalpesh Singh
by
5.6k points